Antihypertensive activity of the ACE–renin inhibitory peptide derived from Moringa oleifera protein. Issue 19 (12th August 2021) - Ma, Keer; Wang, Yujiao; Wang, Mingjie; Wang, Zhigao; Wang, Xuefeng; Ju, Xingrong; He, Rong
Abstract : Moringa oleifera (MO) leaf is a potential plant protein resource with high nutritional and medicinal value. Abstract : Moringa oleifera (MO) leaf is a potential plant protein resource with high nutritional and medicinal value. The study aims to investigate the hypotensive activity and stability of MO leaf peptides. MO leaf protein was extracted and then hydrolyzed with Alcalase to produce the MO leaf protein hydrolysate (MOPH). The MOPH was separated into peptide fractions with different molecular weights by membrane ultrafiltration. The MOPH and ultrafiltration fractions were evaluated for antihypertensive activity. Inhibition of the angiotensin-converting enzyme (84.71 ± 0.07%) and renin (43.72 ± 0.02%) was significantly higher for <1 kDa peptides when compared to other fractions. Oral administration of the <1 kDa component in spontaneously hypertensive rats positively lowers the blood pressure (∼17 mmHg). The <1 kDa component was isolated and purified subsequently; the final active component was identified by mass spectrometry and amino acid sequence analysis. Two highly active ACE (angiotensin-converting enzyme) and renin dual inhibitory peptides Leu-Gly-Phe-Phe (LGF) and Gly-Leu-Phe-Phe (GLFF) were obtained. The two peptides exhibited a good dual inhibitory activity of ACE and renin with IC50 values of LGF (0.29 ± 0.13 mM, 1.88 ± 0.08 mM) and GLFF (0.31 ± 0.04 mM, 2.80 ± 0.08 mM). Furthermore, in vivo models, LGF and GLFF significantly reduced the systolic blood pressure (19.4 mmHg; 18.2 mmHg) and diastolic blood pressure (12 mmHg; 13.8 mmHg) of SHRs (spontaneously hypertensive rats). The peptide transmembrane transport experiments and simulated gastrointestinal digestion experiments with LGF and GLFF showed that they can resist gastrointestinal digestion in a complete form. Thus, bioactive peptides from MO leaf may possess the potential to be used for treating hypertension in humans.